THE EFFECT OF GOVERNMENT ACCOUNTING STANDARD APPLICATION ON THE QUALITY OF FINANCIAL STATEMENTS (STUDY ON REGIONAL APPARATUS ORGANIZATIONS OF KARANGANYAR REGENCY) - Galuh Syarifah Mentari Dahana; Nasyiah Hasanah Purnomowati (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2022)
This research aims to analyze the effect of the implementation of the government accounting standard (Standar Akuntansi Pemerintahan/SAP) on the quality of the financial statements through the study of perceptions of the financial management staff and to analyze the extent to which the government’s internal control system (Sistem Pengendalian Intern Pemerintah/SPIP) strengthens the relationship between government accounting standard implementation and the quality of the financial statements. The samples were taken using the saturated sampling technique. A total of 171 respondents from 57 regional apparatus organizations (Organisasi Perangkat Daerah/OPD) in Karanganyar Regency were invited to participate in this study, with 117 data used for analysis. The data were analyzed using a simple regression test and interaction test. The results of the study show that the implementation of government accounting standards gives a positive effect on the quality of financial statements.